Teachers’ Implementation of Communicative Language Teaching in English Language Teaching - Nurdiana; Iskandar; Munir (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study aims to describe how English teachers implement Communicative Language Teaching (CLT) in English teaching. This study used a qualitative research design. Data were collected through classroom observations, interviews with teachers, and documentation. The findings indicate that teachers implement CLT through various communicative activities such as group discussions, role-plays, presentations, and information gap activities. Teachers act as facilitators by guiding students, providing vocabulary support, and creating opportunities for interaction. However, teachers also face several challenges, including students' lack of confidence, limited vocabulary, and varying levels of English proficiency. To overcome these challenges, teachers provide easy-to-understand instructions, facilitate a comfortable and supportive learning space, and encourage students to speak without fear of making mistakes. This study can conclude that CLT can be implemented effectively when teachers adapt the approach to students' needs and classroom conditions.